2018
DOI: 10.1007/s12192-018-0886-1
|View full text |Cite
|
Sign up to set email alerts
|

NR4A1 contributes to high-fat associated endothelial dysfunction by promoting CaMKII-Parkin-mitophagy pathways

Abstract: Parkin-related mitophagy is vital for endothelial cell viability and the development of atherosclerosis, although the upstream regulatory factor underlying Parkin-mediated mitophagy in endothelial apoptosis and atherosclerosis progression remains unknown. In the present study, we demonstrated that nuclear receptor subfamily 4 group A member 1 (NR4A1) is actually expressed in aortic endothelial cells (AECs) under oxidized low-density lipoprotein (ox-LDL) treatment in vitro or isolated from high-fat treated mice… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
37
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(39 citation statements)
references
References 64 publications
(64 reference statements)
2
37
0
Order By: Relevance
“…Consistently with our findings, previous studies have reported that DUSP1 downregulation was noted in fatty liver disease and cardiac ischemia reperfusion injury (Li et al, ; Pickard, Burke, Davidson, & Yellon, ; Zhou et al, ) via modifying mitochondrial function, and that DUSP1 overexpression or pharmacological activation of DUSP1 retards or prevents the progression of nonalcoholic fatty liver and cardiac ischemia reperfusion injury. Collectively, these observations have demonstrated the sufficiency of DUSP1 to modulate mitochondrial metabolic diseases, which may highlight a new entry point for treating chronic metabolic disorder by targeting DUSP1.…”
Section: Discussionsupporting
confidence: 93%
“…Consistently with our findings, previous studies have reported that DUSP1 downregulation was noted in fatty liver disease and cardiac ischemia reperfusion injury (Li et al, ; Pickard, Burke, Davidson, & Yellon, ; Zhou et al, ) via modifying mitochondrial function, and that DUSP1 overexpression or pharmacological activation of DUSP1 retards or prevents the progression of nonalcoholic fatty liver and cardiac ischemia reperfusion injury. Collectively, these observations have demonstrated the sufficiency of DUSP1 to modulate mitochondrial metabolic diseases, which may highlight a new entry point for treating chronic metabolic disorder by targeting DUSP1.…”
Section: Discussionsupporting
confidence: 93%
“…Interestingly, the JNK pathway has been confirmed to be the upstream signal for mitochondrial fragmentation [18]. Other studies also suggest that CaMKII phosphorylation and Fis1 upregulation also participate into the regulation of mitochondrial fragmentation [44,45]. Based on these findings, we examined whether MKP1 controlled mitochondrial fragmentation via the JNK-CaMKII-Fis1 pathway.…”
Section: Mkp1 Controls Mitochondrial Fragmentation Via Inhibiting Thementioning
confidence: 88%
“…Previous findings demonstrated that parkin was upregulated in the vascular wall of obese, diabetic and atherosclerotic mice, and parkin-related mitophagy is protective in these disease models [21]. Thus, overexpression or activation of parkin potentially serves as a strategy in treating vascular diseases.…”
Section: Discussionmentioning
confidence: 97%